Effect of Temperature Changes on Critical Micelle Concentration for Tween Series surfactant (Global Journal of Science Frontier Research, 2013)
The critical micelle concentration (CMC) for polyoxyethylene sorbitan fatty acid esters (tween) series surfactant was determined by the fluorescence intensity technique. It has been measured against concentration of micelle at temperature range (298-348) °k . at 298°k the CMC for tween (20, 21, 40, 60 and 80) were (0.0499, 0.063, 0.0333, 0.0167 and 0.015) mM respectively. The critical micelle concentration (CMC) for all tween series decreased with increasing carbon atoms number for alkyl group, but increased with increasing the number of oxyethylene group. The CMC for all tween series decreased with increasing temperature, it slightly increased at higher temperature. Thermodynamic parameters (ΔG°m, ΔH°m , ΔS°m) of the micelle formation were calculated from the temperature dependence on the CMC, ΔG°m decreased when increasing temperature above the whole temperature range . It is found that (ΔG°m, ΔH°m, ΔS°m ) decreased with increasing carbon number for alkyl group, but increased with increasing the number of oxyethylene group.
Keywords: CMC; micelle Micellization thermodynamic; nonionic surfactant; Pyrene-3-carboxaldehyde; Tween